A community-based validation of the International Alliance for the Control of Scabies Consensus Criteria by expert and non-expert examiners in Liberia - Walker, Stephen L. (PLoS Negl Trop Dis, 2020)
BACKGROUND: The International Alliance for the Control of Scabies (IACS) recently published expert consensus criteria for scabies diagnosis. Formal validation of these criteria is needed to guide implementation. We conducted a study to provide detailed description of the morphology and distribution of scabies lesions as assessed by dermatologists and validate the IACS criteria for diagnosis by both expert and non-expert examiners. METHODS: Participants from a community in Monrovia, Liberia, were independently assessed by two dermatologists and six non-expert examiners. Lesion morphology and distribution were documented based on the dermatologist examination. Diagnoses were classified by IACS criteria and the sensitivity and specificity of non-expert examiner assessments calculated. RESULTS: Papules were the most common lesions (97.8%). Burrows were found in just under half (46.7%) and dermatoscopy was positive in a minority (13.3%). Scabies lesions were found in all body regions but more than 90% of patients could have been diagnosed by an examination of only the limbs. Severity of itch was associated with lesion number (p = 0.003). The sensitivity of non-expert examiners to detect typical scabies ranged between 69–83% and specificity 70–96%. The sensitivity of non-expert examiners was higher in more extensive disease (78–94%). CONCLUSIONS: The IACS criteria proved a valid tool for scabies diagnosis. For the purposes of implementation papules and burrows represent truly ‘typical’ scabies lesions. Non-expert examiners are able to diagnose scabies with a high degree of accuracy, demonstrating they could form a key component in population-level control strategies.